Autoproscoptae, Bogomils and Messalians in the 14th Century Bulgaria - Wolski, Jan Mikołaj (Studia Ceranea, 2014)
This paper discusses the use of the names of heresies: bogomilism, messalianism and the heresy of autoproscoptae in 14th century Bulgarian sources. The author underlines that the names of bogomilism and messalianism do not always refer to dualism. Two wider unknown examples of such use of the name “messalinism” are recalled. In the Pseudo-Zonaras Nomocanon (CIAI 1160), the name “messalianism” is treated as being equal to the “heresy of autoproscoptae”. In the Rule for hermits, messalians are presented not as heretics, but as monks disregarding their rules.